Urgency of E-Commerce Act for Consumer Protection (Comparative Study in Indonesia, Singapore, and China) - Cahyaningsih, Diana Tantri; Kharisma, Dona Budi; Agnjana, Goldwina Aphroditerri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to discover the problems of regulation of electronic commerce (e-commerce) in Indonesia, Singapore, and China with a focus on Indonesia. This study also intends to construct e-commerce legislation to promote the expansion of the digital economy in many nations. This study focuses on legal research. Comparative and legal approaches are utilized in the study process. The legal documents utilized are e-commerce laws in Indonesia, Singapore, and China. In pandemic era, Indonesian e-commerce transactions had climbed by 50.8% with transactions reaching IDR 401 trillion. However, fraud in online transactions is one of the most reported crimes. As many as 28.7% of cybercrimes originate from fraud. The number of fraud cases, transaction security, and weak protection of personal data consumers are still central issues. The Information and Electronic Transactions Act, as revised by Act Number 19/2016 does not explicitly regulate e-commerce. Compared to Singapore, it has a Casetrust to increase consumer confidence and is supported by the Electronic Transactions Act (ETA).  Personal Data Protection Act 2012 (PDPA). E-commerce Act of the People’s Republic of China is supported by Personal Information Protection Act of the People's Republic of China.  The Act aims to give some legal certainty and predictability to online businesses.